Annual Plan 1994-95 Draft Proposals Volume-II Sectoral Programmes Economic Services Government of Meghalaya - Planning Commission (Planning Commission, 1994)
Meghalaya has a population of 17,74,778 (1991-Census) distributed over an area of approximately 22,500 Square Kms. The gross cropped area is 2.39 lakh hectares (provisional) while the net cropped area is 2.01 lakh hectares. A target of gross cropped area of 2.45 lakh hectares and net cropped area of 2.00 lakh hectares is proposed for the year 1994-95 against the anticipated gross cropped area of 2.40 lakh hectares during 1993-94.
Planning Department Government of Meghalaya